Answer:
perimeter: 4x+2 area: x^2+x
Step-by-step explanation:
for perimeter, you add x+x+x+x+1+1, which is 4x+2
for area, you multiply x*x+1, which would be x^2+x
Answer:
1.
÷
---> ![\frac{-3x + 2}{3(3x - 1)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-3x%20%2B%202%7D%7B3%283x%20-%201%29%7D%20)
2.
---> ![\frac{2(6x - 1)}{(3x - 1)(-3x + 2)}](https://tex.z-dn.net/?f=%5Cfrac%7B2%286x%20-%201%29%7D%7B%283x%20-%201%29%28-3x%20%2B%202%29%7D)
3.
---> ![\frac{-2(12x - 5)}{(3x - 1)(-3x + 2)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-2%2812x%20-%205%29%7D%7B%283x%20-%201%29%28-3x%20%2B%202%29%7D%20)
4.
--> ![\frac{12}{(3x - 1)(-3x + 2)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B12%7D%7B%283x%20-%201%29%28-3x%20%2B%202%29%7D%20)
Step-by-step explanation:
Given that:
1. ![P(x) = \frac{2}{3x - 1}](https://tex.z-dn.net/?f=%20P%28x%29%20%3D%20%5Cfrac%7B2%7D%7B3x%20-%201%7D%20)
![Q(x) = \frac{6}{-3x + 2}](https://tex.z-dn.net/?f=%20Q%28x%29%20%3D%20%5Cfrac%7B6%7D%7B-3x%20%2B%202%7D%20)
Thus,
÷
=
÷ ![\frac{6}{-3x + 2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B6%7D%7B-3x%20%2B%202%7D%20)
Flip the 2nd function, Q(x), upside down to change the process to multiplication.
![\frac{2}{3x - 1}*\frac{-3x + 2}{6}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%7D%7B3x%20-%201%7D%2A%5Cfrac%7B-3x%20%2B%202%7D%7B6%7D%20)
![\frac{2(-3x + 2)}{6(3x - 1)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%28-3x%20%2B%202%29%7D%7B6%283x%20-%201%29%7D%20)
![= \frac{-3x + 2}{3(3x - 1)}](https://tex.z-dn.net/?f=%20%3D%20%5Cfrac%7B-3x%20%2B%202%7D%7B3%283x%20-%201%29%7D%20)
2.
= ![\frac{2}{3x - 1} + \frac{6}{-3x + 2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%7D%7B3x%20-%201%7D%20%2B%20%5Cfrac%7B6%7D%7B-3x%20%2B%202%7D%20)
Make both expressions as a single fraction by finding, the common denominator, divide the common denominator by each denominator, and then multiply by the numerator. You'd have the following below:
![\frac{2(-3x + 2) + 6(3x - 1)}{(3x - 1)(-3x + 2)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%28-3x%20%2B%202%29%20%2B%206%283x%20-%201%29%7D%7B%283x%20-%201%29%28-3x%20%2B%202%29%7D%20)
![\frac{-6x + 4 + 18x - 6}{(3x - 1)(-3x + 2)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-6x%20%2B%204%20%2B%2018x%20-%206%7D%7B%283x%20-%201%29%28-3x%20%2B%202%29%7D%20)
![\frac{-6x + 18x + 4 - 6}{(3x - 1)(-3x + 2)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-6x%20%2B%2018x%20%2B%204%20-%206%7D%7B%283x%20-%201%29%28-3x%20%2B%202%29%7D%20)
![\frac{12x - 2}{(3x - 1)(-3x + 2)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B12x%20-%202%7D%7B%283x%20-%201%29%28-3x%20%2B%202%29%7D%20)
![= \frac{2(6x - 1}{(3x - 1)(-3x + 2)}](https://tex.z-dn.net/?f=%20%3D%20%5Cfrac%7B2%286x%20-%201%7D%7B%283x%20-%201%29%28-3x%20%2B%202%29%7D%20)
3.
= ![\frac{2}{3x - 1} - \frac{6}{-3x + 2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%7D%7B3x%20-%201%7D%20-%20%5Cfrac%7B6%7D%7B-3x%20%2B%202%7D%20)
![\frac{2(-3x + 2) - 6(3x - 1)}{(3x - 1)(-3x + 2)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%28-3x%20%2B%202%29%20-%206%283x%20-%201%29%7D%7B%283x%20-%201%29%28-3x%20%2B%202%29%7D%20)
![\frac{-6x + 4 - 18x + 6}{(3x - 1)(-3x + 2)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-6x%20%2B%204%20-%2018x%20%2B%206%7D%7B%283x%20-%201%29%28-3x%20%2B%202%29%7D%20)
![\frac{-6x - 18x + 4 + 6}{(3x - 1)(-3x + 2)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-6x%20-%2018x%20%2B%204%20%2B%206%7D%7B%283x%20-%201%29%28-3x%20%2B%202%29%7D%20)
![\frac{-24x + 10}{(3x - 1)(-3x + 2)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-24x%20%2B%2010%7D%7B%283x%20-%201%29%28-3x%20%2B%202%29%7D%20)
![= \frac{-2(12x - 5}{(3x - 1)(-3x + 2)}](https://tex.z-dn.net/?f=%20%3D%20%5Cfrac%7B-2%2812x%20-%205%7D%7B%283x%20-%201%29%28-3x%20%2B%202%29%7D%20)
4. ![P(x)*Q(x) = \frac{2}{3x - 1}* \frac{6}{-3x + 2}](https://tex.z-dn.net/?f=%20P%28x%29%2AQ%28x%29%20%3D%20%5Cfrac%7B2%7D%7B3x%20-%201%7D%2A%20%5Cfrac%7B6%7D%7B-3x%20%2B%202%7D%20)
![P(x)*Q(x) = \frac{2*6}{(3x - 1)(-3x + 2)}](https://tex.z-dn.net/?f=%20P%28x%29%2AQ%28x%29%20%3D%20%5Cfrac%7B2%2A6%7D%7B%283x%20-%201%29%28-3x%20%2B%202%29%7D%20)
![P(x)*Q(x) = \frac{12}{(3x - 1)(-3x + 2)}](https://tex.z-dn.net/?f=%20P%28x%29%2AQ%28x%29%20%3D%20%5Cfrac%7B12%7D%7B%283x%20-%201%29%28-3x%20%2B%202%29%7D%20)
2.5y + 1.1x ∠ 10
2.5y = - 1.1x +10
y = (- 1.1/2.5)x + 4
Draw this function. It's descending (m negative). All values on the left of the lines satisfy this inequality
Answer:
It decreases.
Step-by-step explanation:
10 / d
Lets say that it was 10 / 40, which is 10 divided by 40, 0.25.
Now, it has increased to twice the amount of that.
1 / 80, 10 divided by 80, which is 0.125
So, it decreases.
88.23%
Simply plug 15/17 into you calculator
and it will give you a decimal, in this case it should be .88235294...
simply move the decimal back to placements and you should have
88.235294... thats still a lot of numbers so just reduce it to 2 places after the decimal and add a percent sign
88.23%
and your done :) this works for any similar problems
I hope this helps